WiSE CRT Is Beneficial for Heart Failure Patients as a Rescue Therapy: Evidence From a Meta-Analysis - Cang, Jiehui; Liu, Yaowu; Zhu, Didi; Liu, Shangshang; Shen, Junxian; Miao, Hongyu; Zhou, Qianxing; Chen, Long (Frontiers in Cardiovascular Medicine, 2022)
Background Leadless endocardial left ventricular (LV) pacing resynchronization therapy is a novel solution for patients with heart failure (HF) in whom conventional cardiac resynchronization therapy (CRT) failed. Methods PubMed and the Cochrane Library were searched for relevant cohort studies. Clinical outcomes of interest such as ejection fraction (EF), QRS duration (QRSd), and left ventricular end-systolic volume (LVESV) were extracted and analyzed. Results Five studies involving 175 HF patients for WiSE CRT were included, and patients were followed-up for 6 months. The implanted success rate ranged from 76.5 to 100%. WiSE CRT resulted in significantly narrower QRSd [mean difference (MD): −38.21 ms, 95% confidence interval (CI): −44.36 to −32.07, p < 0.001], improved left ventricular ejection fraction (MD: 6.07%, 95% CI: 4.43 to 7.71, I2 = 0%, p < 0.001), reduced left ventricular end-systolic volume (MD: −23.47 ml, 95% CI: −37.18 to −9.13, p < 0.001), and reduced left ventricular end-diastolic volume (MD: −24.02 ml, 95% CI: −37.01 to −11.03, p = 0.02). Conclusion Evidence from current studies suggests that leadless endocardial LV pacing resynchronization is effective for HF patients who failed conventional CRT or needed a device upgrade, and it may be an interesting rescue therapy.